KEDUDUKAN MORAL DAN HUKUM DALAM BANGUNAN HUKUM INDONESIA - Taufik Firmanto (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
Discoursing between law and morality is an interesting conversation among a legal scholars and jurists. Observing of legal developments are reviewed historically, the morality of jurisprudence from time to time undergoes sharp reductions. In the early stages of modern human civilization, the morality of jurisprudence still stands firmly on the foundation of the religion (christian). Moral judgments about good or bad, right or wrong, are consistently restored to the divine rules. Faced with the power of the church and the kings, came the antithesis of contradictory extreme thought, the idea that denied the existence of God or rejected the hegemony of religion and the church. The opposing of two rivals in concepts, theories and practices are concerning of the moral role of life. In turn, it had a significant influence on the development of jurisprudence in Europe at the time, leading to the spread of colonization in the eastern hemisphere.